Genetic and genomic approaches for the discovery of parasite genes involved in antimalarial drug resistance. Issue 12 (9th August 2013) - MWANGI, JONATHAN M.; RANFORD-CARTWRIGHT, LISA C.
SUMMARY: The biggest threat to the war on malaria is the continued evolution of drug resistance by the parasite. Resistance to almost all currently available antimalarials now exists in Plasmodium falciparum which causes the most suffering among all human malaria parasites. Monitoring of antimalarial efficacy and the development and subsequent spread of resistance has become an important part in the treatment and control of malaria. With recent reports of reduced efficacy of artemisinin, the current recommended treatment for uncomplicated malaria, there is urgent need for better methods to recognize and monitor drug resistance for effective treatment. Molecular markers have become a welcome addition to complement the more laborious and costly in vitro and in vivo methods that have traditionally been used to monitor drug resistance. However, there are currently no molecular markers for resistance to some antimalarials. This review highlights the role of the various genetic and genomic approaches that have been used in identifying the molecular markers that underlie drug resistance in P. falciparum . These approaches include; candidate genes, genetic linkage and genome-wide association studies. We discuss the requirements and limitations of each approach and use various examples to illustrate their contributions in identifying genomic regions of the parasite associated with antimalarial drug responses.